(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
The most common use of wood in construction is for bending elements. The calculation of bending members made of glued laminated timber requires the use of the section modulus of this member and the calculated values of the bending strength of the timber. The design bending strength of wood is determined based on the characteristic values obtained from the laws of elastic material under load. However, this statement completely contradicts the anisotropy of wood in its tensile and compressive behavior. If it is known that wood works 90-95% to failure in longitudinal tension, it is then it can be assumed that it is elastic at all. However, in longitudinal deformation, there is non-linear behavior with increasing elastic and plastic strains. Furthermore, the longitudinal tensile strength of wood is almost twice that of longitudinal compression. Therefore, even if the relative deformations in the wood are the same different compressive and tensile stresses arise in the bending element, i.e. Many authors who have carried out experimental and theoretical studies on the performance of timber beams have pointed out that the neutral force line in the cross-section of the element in direct transverse bending, with increasing levels of single load, shifts towards the tensile zone. Therefore, using the moment of resistance of the cross section in the wooden element to determine the section modulus is incorrect. The moment of resistance of a section of a timber member is only determined if the centre of gravity of the section coincides with the centre of force line. Usually, the failure of long wooden beams in transverse bending usually occurs due to the fracture of the most stressed outer layers of wood in the of the tensile area and is brittle in nature. It is on such elements that the the temporary bending strength. It is on such elements that the bending strength is crucial. However, the values of m f , usually determined in the outermost wood layers of the tensile zone, based on the condition, only reach values of 70-75% of the longitudinal tensile strength of wood. It is not possible to determine the tensile strength of wood at this stress level. Therefore, the results of determining the bending strength of wood using the moment of resistance of the cross-section of a timber element determined in the limiting condition are erroneous due to the impossibility of establishing W values.